A proposed scheme for the monitoring of antibiotic resistance in veterinary pathogens of food animals in the UK. (1st March 2021) - Teale, Christopher; Borriello, Peter
Abstract: Background : Antibiotic resistance in bacteria is a global threat to both animal and public health, and detecting its occurrence is an important component of control strategies. Monitoring programmes for antibiotic resistance are currently in place in food‐producing animals in the European Union covering the zoonotic bacteria Salmonella enterica, Campylobacter coli and Campylobacter jejuni and the indicator bacteria Escherichia coli, Enterococcus faecalis and Enterococcus faecium . However, there is no equivalent pan‐European statutory monitoring programme covering the antibiotic susceptibility of veterinary bacterial pathogens in food animals. This paper considers that issue and aims to facilitate and stimulate further discussion. Methods : Recommendations, proposed by the authors from the scientific literature and following expert discussion at international meetings, are presented for monitoring the susceptibility of key veterinary pathogens. Results : The selected veterinary pathogens comprise Actinobacillus pleuropneumoniae, Bordetella bronchiseptica, E. coli, Histophilus somni, Mannheimia haemolytica, Pasteurella multocida, Staphylococcus aureus and Streptococcus spp. from the major food animal species cattle, pigs and poultry. The organisms are tested using harmonised panels of antibiotics over specified dilution ranges in a broth microdilution method. Conclusion : The selected antibiotics and their respective dilution ranges are presented together with the underlying rationale for inclusion; the ranges chosen are suitable for incorporation into three microtitre plates, with each organism tested using a single plate. The recommendations are being implemented in 2020 in the UK for monitoring of the susceptibility of veterinary bacterial pathogens.